Nuclear Met promotes hepatocellular carcinoma tumorigenesis and metastasis by upregulation of TAK1 and activation of NF-κB pathway. (28th December 2017) - Tey, Sze Keong; Tse, Edith Yuk Ting; Mao, Xiaowen; Ko, Frankie Chi Fat; Wong, Alice Sze Tsai; Lo, Regina Cheuk-Lam; Ng, Irene Oi-Lin; Yam, Judy Wai Ping
Abstract: Presence of Met receptor tyrosine kinase in the nucleus of cells has been reported. However, the functions of Met which expresses in the nucleus (nMet) remain elusive. In this study, we found that nMet was increased in 89% of HCC tumorous tissues when compared with the corresponding non-tumorous liver tissues. nMet expression increased progressively along HCC development and significantly correlated with cirrhosis, poorer cellular differentiation, venous invasion, late stage HCC and poorer overall survival. Western blot analysis revealed that nMet is a 48-kDa protein comprising the carboxyl terminal of Met receptor. Induced expression of nMet promoted HCC cell growth, migration and invasiveness in vitro and tumorigenesis and pulmonary metastasis in vivo . Luciferase assay showed that nMet activated NF-κB pathway. Indeed, p-IKKα/β and nuclear p-p65 were higher in nMet stable cells than in the control cells. Perturbation of TAK1/NF-κB axis abrogated the aggressiveness of HCC cells, both in vitro and in vivo . In conclusion, nMet was overexpressed and as a potential prognostic biomarker of HCC. Functionally, nMet accelerated HCC tumorigenesis and metastasis via the activation of TAK1/NF-κB pathway. Highlights: nMet is overexpressed in human HCCs and is a potential prognostic factor for HCC patients. nMet is a truncated cytoplasmic domain of Met surface receptor. nMet promotes HCC tumorigenesis and metastasis in vivo . Crosstalk between nMet and TAK1/NF-κB pathway leading to the aggressiveness of HCC cells.